A missense mutation in TUBD1 is associated with high juvenile mortality in Braunvieh and Fleckvieh cattle. (December 2016) - Schwarzenbacher, Hermann; Burgstaller, Johann; Seefried, Franz; Wurmser, Christine; Hilbe, Monika; Jung, Simone; Fuerst, Christian; Dinhopl, Nora; Weissenböck, Herbert; Fuerst-Waltl, Birgit; Dolezal, Marlies; Winkler, Reinhard; et al.
Abstract Background Haplotypes with reduced or missing homozygosity may harbor deleterious alleles that compromise juvenile survival. A scan for homozygous haplotype deficiency revealed a short segment on bovine chromosome 19 (Braunvieh haplotype 2, BH2) that was associated with high juvenile mortality in Braunvieh cattle. However, the molecular genetic underpinnings and the pathophysiology of BH2 remain to be elucidated. Results The frequency of BH2 was 6.5 % in 8, 446 Braunvieh animals from the national bovine genome databases. Both perinatal and juvenile mortality of BH2 homozygous calves were higher than the average in Braunvieh cattle resulting in a depletion of BH2 homozygous adult animals (P = 9.3x10−12 ). The analysis of whole-genome sequence data from 54 Braunvieh animals uncovered a missense mutation inTUBD1 (rs383232842, p.H210R) that was compatible with recessive inheritance of BH2. The availability of sequence data of 236 animals from diverse bovine populations revealed that the missense mutation also segregated at a low frequency (1.7 %) in the Fleckvieh breed. A validation study in 37, 314 Fleckvieh animals confirmed high juvenile mortality of homozygous calves (P = 2.2x10−15 ). Our findings show that the putative disease allele is located on an ancestral haplotype that segregates in Braunvieh and Fleckvieh cattle. To unravel the pathophysiology of BH2, six homozygous animals were examined at the animal clinic. Clinical and pathological findings revealed that homozygous calves suffered from chronic airway disease possibly resulting from defective cilia in the respiratory tract. Conclusions A missense mutation inTUBD1 is associated with high perinatal and juvenile mortality in Braunvieh and Fleckvieh cattle. The mutation is located on a common haplotype likely originating from an ancient ancestor of Braunvieh and Fleckvieh cattle. Our findings demonstrate for the first time that deleterious alleles may segregate across closed cattle breeds without recent admixture. Homozygous calves suffer from chronic airway disease resulting in poor growth performance and high juvenile mortality. The respiratory manifestations resemble key features of diseases resulting from impaired function of airway cilia.